Trends in primary central nervous system lymphoma incidence and survival in the U.S. (28th March 2016) - Shiels, Meredith S.; Pfeiffer, Ruth M.; Besson, Caroline; Clarke, Christina A.; Morton, Lindsay M.; Nogueira, Leticia; Pawlish, Karen; Yanik, Elizabeth L.; Suneja, Gita; Engels, Eric A.
Summary: It is suspected that primary central nervous system lymphoma (PCNSL) rates are increasing among immunocompetent people. We estimated PCNSL trends in incidence and survival among immunocompetent persons by excluding cases among human immunodeficiency virus (HIV)‐infected persons and transplant recipients. PCNSL data were derived from 10 Surveillance, Epidemiology and End Results (SEER) cancer registries (1992–2011). HIV‐infected cases had reported HIV infection or death due to HIV. Transplant recipient cases were estimated from the Transplant Cancer Match Study. We estimated PCNSL trends overall and among immunocompetent individuals, and survival by HIV status. A total of 4158 PCNSLs were diagnosed (36% HIV‐infected; 0·9% transplant recipients). HIV prevalence in PCNSL cases declined from 64·1% (1992–1996) to 12·7% (2007–2011), while the prevalence of transplant recipients remained low. General population PCNSL rates were strongly influenced by immunosuppressed cases, particularly in 20–39 year‐old men. Among immunocompetent people, PCNSL rates in men and women aged 65+ years increased significantly (1·7% and 1·6%/year), but remained stable in other age groups. Five‐year survival was poor, particularly among HIV‐infected cases (9·0%). Among HIV‐uninfected cases, 5‐year survival increased from 19·1% (1992–1994) to 30·1% (2004–2006). In summary, PCNSL rates have increased among immunocompetent elderly adults, but not in younger individuals. Survival remains poor for both HIV‐infected and HIV‐uninfected PCNSL patients.